2009
DOI: 10.1111/igc.0b013e3181b7a1d5
|View full text |Cite
|
Sign up to set email alerts
|

Pure Papillary Serous Tumors of the Endometrium

Abstract: Papillary serous carcinoma of the endometrium is a very aggressive type of endometrial carcinoma that behaves more similar to ovarian carcinoma than to endometrial carcinoma. Tumor markers at diagnosis, stage, and myometrial infiltration mainly determine prognosis at our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Consistent with previous reports, 36 USC stage II/III/IV had a higher recurrence rate in comparison to stage-matched EAC (40% Vs 22%), as well, a shorter time to relapse (5.8 months for USC vs 15.9 months for EAC). Additionally, patients with USC had worse OS of 37.2% compared to EAC 62.7%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous reports, 36 USC stage II/III/IV had a higher recurrence rate in comparison to stage-matched EAC (40% Vs 22%), as well, a shorter time to relapse (5.8 months for USC vs 15.9 months for EAC). Additionally, patients with USC had worse OS of 37.2% compared to EAC 62.7%.…”
Section: Discussionsupporting
confidence: 91%
“…15 Benito et al analyzed USC tumors and found that the depth of invasion had an independent influence on OS in multivariate analysis. 6 In our series, depth of MI was the single most important factor in uterine carcinoma. MI of >50% was an independent factor in predicting DOD, OS and any poor outcome (recurrence, progression or persistence of disease) in stage II/III/IV cancer.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…USC is responsible for a disproportionate number of deaths due to the fact that most of these tumors have already spread outside the uteri corpus. The 5-year survival rate for stages I–II EAC is estimated to range between 75 and 87%, and between 44 and 50% for stages I–II USC [34]. Numerous prognostic parameters have been implicated in endometrial carcinoma including tumor grade, tumor subtypes, tumor stage, presence of lymphovascular invasion (LVI), and depth of myometrial invasion [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…They are high grade tumors with deep myometrial invasion and lymphovascular involvement [5]. The 5-year survival rates are estimated to be 50% for stage II, 20% for stage III and 5–10% for stage IV disease [6].…”
Section: Introductionmentioning
confidence: 99%